CHILDHOOD TUBERCULOSIS: A CROSS-SECTIONAL STUDY OF PREVENTIVE PRACTICES AMONG MOTHERS OF TODDLERS IN INDONESIA - Rifdah, Zalfa’ul; Nafisah, Lu’lu; Hariyadi, Bambang (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Tuberculosis (TB) control and prevention in children is a global health priority. Despite various preventive efforts undertaken by the South Purwokerto Community Health Center, the incidence of childhood TB continues to rise. Purpose: This study aimed to determine the behaviors of toddlers' mothers in preventing TB in children in Teluk Subdistrict, South Purwokerto. Methods: This study employed an analytical observational design with a cross-sectional approach. The population comprised 522 mothers of toddlers in Teluk Subdistrict, with a sample of 81 respondents selected through a multi-stage sampling procedure involving cluster and purposive sampling from integrated healthcare centers in several community units. Primary data were collected using a questionnaire in November 2023. Data analysis involved chi-square tests and multiple logistic regression. Results: The findings revealed a significant association between mothers' attitudes (p-value = 0.02) and healthcare workers' support (p-value = 0.003) and their behaviors in preventing childhood TB. Conversely, variables such as education level (p-value = 0.78), occupation (p-value = 0.51), knowledge (p-value = 0.90), and information access (p-value = 0.10) showed no significant relationship. Logistic regression analysis indicated that healthcare workers' support was the most influential factor in determining mothers' behaviors in preventing childhood TB (p-value = 0.02) (OR = 3.53). Conclusion: Healthcare workers' support emerged as the primary determinant of mothers' behaviors in preventing childhood TB in Teluk Subdistrict, South Purwokerto.